Porous Dithiine-Linked Covalent Organic Framework as a Dynamic Platform for Covalent Polysulfide Anchoring in Lithium-Sulfur Battery Cathodes - Haldar, Sattwick; Wang, Mingchao; Bhauriyal, Preeti; Hazra, Arpan; Khan, Arafat H.; Bon, Volodymyr; Isaacs, Mark A.; De, Ankita; Shupletsov, Leonid; Boenke, Tom; Grothe, Julia; Heine, Thomas; et al. (Journal of the American Chemical Society, 2022)
Dithiine linkage formation via a dynamic and self-correcting nucleophilic aromatic substitution reaction enables the de novo synthesis of a porous thianthrene-based two-dimensional covalent organic framework (COF). For the first time, this organo-sulfur moiety is integrated as a structural building block into a crystalline layered COF. The structure of the new material deviates from the typical planar interlayer π-stacking of the COF to form undulated layers caused by bending along the C-S-C bridge, without loss of aromaticity and crystallinity of the overall COF structure. Comprehensive experimental and theoretical investigations of the COF and a model compound, featuring the thianthrene moiety, suggest partial delocalization of sulfur lone pair electrons over the aromatic backbone of the COF decreasing the band gap and promoting redox activity. Postsynthetic sulfurization allows for direct covalent attachment of polysulfides to the carbon backbone of the framework to afford a molecular-designed cathode material for lithium-sulfur (Li-S) batteries with a minimized polysulfide shuttle. The fabricated coin cell delivers nearly 77% of the initial capacity even after 500 charge-discharge cycles at 500 mA/g current density. This novel sulfur linkage in COF chemistry is an ideal structural motif for designing model materials for studying advanced electrode materials for Li-S batteries on a molecular level.
CRIS-Team Scopus Importer:2023-03-20